Highly efficient, cell reversal resistant PEMFC based on PtNi/C octahedral and OER composite catalyst. (18th March 2020) - Wang, Jue; Zhou, Xiangyang; Li, Bing; Yang, Daijun; Lv, Hong; Xiao, Qiangfeng; Ming, Pingwen; Wei, Xuezhe; Zhang, Cunman
Abstract: In order to obtain a fuel cell with both enhanced power generation performance and cell reversal resistance, the composite catalyst consisting of the self-made PtNi/C octahedral and the oxygen evolution reaction (OER) catalyst IrO2 and RuO2 is mixed and applied in the anode, and the only octahedral catalyst is employed as the cathode to prepare the membrane electrode assembly (MEA). The electrochemical activity of the composite catalyst decreases slightly, but its performance retention after the accelerated durability test (ADT) is higher. In the single cell test, the MEA fabricated using the composite catalyst maintains good single cell power generation performance. Compared with the control fabricated with Pt/C (JM), the cell voltage at 1 A cm −2 and the maximum power density are increased by 23 mV and 119 mW cm −2, respectively. Especially, its durability under continuous cell reversal condition is also improved significantly, and the holding time is prolonged by 1 h. This work realizes the transformation of the octahedral catalyst from the laboratory research to the actual application, and solves the difficulties in fuel cell application, and promotes its commercialization. Graphical abstract: Image 1 Highlights: PtNi/C Oct and OER catalyst are prepared and mixed to composite catalyst. MEA is prepared with PtNi/C Oct in cathode and composite catalyst in anode. This MEA shows good power generation performance and cell reversal durability. This work realizes actual application of Pt-based octahedral catalyst in PEMFC.